"What shall we do with the Negro?" : Lincoln, white racism, and Civil War America - Escott, Paul D., 1947- (University of Virginia Press, 2009)
Consulting a broad range of contemporary newspapers, magazines, books, army records, government documents, publications of citizens' organizations, letters, diaries, and other sources, Paul D. Escott examines the attitudes and actions of Northerners and Southerners regarding the future of African Americans after the end of slavery. --from publisher description.